Chemically Converted Graphene as a Hole Transport Layer (HTL) Inorganic Photovoltaics (OPVS) - Haque, Farjana; Rahman, Md. Moshiur; Al Mahmud, Md. Abdullah; Reza, M. Subbir; Akter, Munmun; Karim, A.H.M Zadidul (Engineering International, 2018)
Concerns about Global Warming and diminishing fossil fuel reserves have accelerated the search for low cost sources of renewable energy. Organic photovoltaics (OPVs) could be one such source; however, they have a list of shortcomings, including low efficiencies, short lifetimes, and reliance on poly (3, 4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT: PSS), an expensive and highly acidic (pH = 1) hole transport layer. Replacing PEDOT: PSS with chemically derived graphene may eliminate one of the drawbacks associated with OPVs. This paper took the first step towards that goal by developing a process to synthesize and characterize inverted and normal poly (3-hexylthiophene) (P3HT), [6, 6]-phenyl-C61 butyric acid methyl ester (PCBM) solar cells. Although detrimental to the stability of the cells, ambient synthesis replicated the conditions required for large-scale, industrial production. The utilization of graphene oxide (GO) thin films as the hole transport and electron blocking layer in organic photovoltaics (OPVs) is demonstrated. The incorporation of GO deposited from neutral solutions between the photoactive poly(3-hexylthiophene) (P3HT):phenyl-C61 butyric acid methyl ester (PCBM) layer and the transparent and conducting indium tin oxide (ITO) leads to a decrease in recombination of electrons and holes and leakage currents. This results in a dramatic increase in the OPV efficiencies to values that are comparable to devices fabricated with PEDOT: PSS as the hole transport layer. Our results indicate that GO could be a simple solution process able Alternative to PEDOT: PSS as the effective hole transport and electron blocking layer in OPV and light-emitting diode devices.
Keywords: Organic photovoltaics (OPVs); Graphene oxide (GO); poly (3, 4-ethylenedioxythiophene) polystyrene sulfonate